The impact of the Real Time Gross Settlement System (RTGS) on the financial performance of Bahraini banks (2012-2021) - Standard Study – - Sofia Zemmit; Ismail Dahmani (Journal of North African Economies, 2025)
This study aimed to highlight the impact of the Real Time Gross Settlement System (RTGS) on the financial performance indicators of Bahraini banks. In order to achieve the objective of the study and test its hypotheses, a simple linear model was used as a standard statistical tool for applying statistical tests and selecting the most appropriate ones statistically. The results of the standard study showed that the (RTGS) system has a positive impact on the financial performance indicators (NPLS, ROE) of Bahraini banks. The Real Time Gross Settlement System affects directly the Return on Equity (ROE) index, and affects indirectly the Non-Performing Loans (NPLS) index, i.e. reducing provisions for Non-Performing Loan risks and raising shareholder profits. As for its effect on the Liquidity Ratio (LR), it was indirectly negative compared to the fixed ratio (LR).